Dual-enzymatically cross-linked gelatin hydrogel enhances neural differentiation of human umbilical cord mesenchymal stem cells and functional recovery in experimental murine spinal cord injury. Issue 2 (8th December 2020) - Yao, Minghao; Li, Jinrui; Zhang, Junni; Ma, Shanshan; Wang, Luyu; Gao, Feng; Guan, Fangxia
Abstract : A dual-enzymatically cross-linked gelatin hydrogel is proposed to undergo direct neuronal differentiation of hUC-MSCs for promoting regeneration of spinal cord injury mice. Abstract : Recently, an advanced stem cell and tissue engineering approach has been recognized as an emerging and fascinating strategy to promote neural repair in spinal cord injury (SCI). Hydrogels can be properly engineered to encapsulate cells, enhance cell viability and neural differentiation, and provide the advantage of flexible adaptation to irregular defects. In this study, a dual-enzymatically cross-linked gelatin hydrogel with hydrogen horseradish peroxidase (HRP) and galactose oxidase (GalOx) was proposed to combine human umbilical cord mesenchymal stem cells (hUC-MSCs) for facilitating nerve regeneration post-SCI. In vitro, hUC-MSCs in this 3D gelatin hydrogel displayed good viability, proliferation, and neuronal differentiation. To further evaluate the neural regeneration effect of hUC-MSCs loaded into gelatin hydrogels in vivo, a clinically-relevant and force-controlled contusion model of mouse spinal cords was established. We found that implantation of a hydrogel loaded with hUC-MSCs significantly promoted the motor function recovery evaluated by Basso Mouse Scale (BMS) and footprint tests. Further histological analysis showed that the hydrogel and hUC-MSC combined transplantation dramatically decreased inflammation, inhibited apoptosis and promoted neurogenesis. Overall, implantation of this dual-enzymatically cross-linked and MSC-laden 3D gelatin hydrogel is a promising therapeutic strategy for SCI treatment.